Toxicological Evaluation of a Probiotic-Based Delivery System for P8 Protein as an Anti-Colorectal Cancer Drug - An BC; Yoon YS; Park HJ; Park S; Kim TY; Ahn JY; Kwon D; Choi O; Heo JY; Ryu Y; Kim JH; Eom H; et al. (Dove Medical Press, 2021)
Byung Chull An,1 Yeo-Sang Yoon,1 Ho Jin Park,1 Sangkyun Park,1 Tai Yeub Kim,1 Jun Young Ahn,1 Daebeom Kwon,1 Oksik Choi,1 Jin Young Heo,1 Yongku Ryu,1 Joong-Hyun Kim,2 Heejong Eom,2 Myung Jun Chung1 1R&D Center, Cell Biotech, Co., Ltd., Gimpo-si, Gyeonggi-do, Korea; 2Laboratory Animal Center, Osong Medical Innovation Foundation, Chungbuk, Cheongju, 28160, KoreaCorrespondence: Myung Jun Chung Tel +82-31-987-6205Fax +82-31-987-6216Email ceo@cellbiotech.comPurpose: This study aimed to toxicological evaluate a probiotics-based delivery system for p8 protein as an anti-colorectal cancer drug.Introduction: Lactic acid bacteria (LAB) have been widely ingested for many years and are regarded as very safe. Recently, a Pediococcus pentosaceus SL4 (PP) strain that secretes the probiotic-derived anti-cancer protein P8 (PP-P8) has been developed as an anti-colorectal cancer (CRC) biologic by Cell Biotech. We initially identified a Lactobacillus rhamnosus (LR)-derived anti-cancer protein, P8, that suppresses CRC growth. We also showed that P8 penetrates specifically into CRC cells (DLD-1 cells) through endocytosis. We then confirmed the efficacy of PP-P8, showing that oral administration of this agent significantly decreased tumor mass (∼ 42%) relative to controls in a mouse CRC xenograft model. In terms of molecular mechanism, PP-P8 induces cell-cycle arrest in G2 phase through down-regulation of Cyclin B1 and Cdk1. In this study, we performed in vivo toxicology profiling to obtain evidence that PP-P8 is safe, with the goal of receiving approval for an investigational new drug application (IND).Methods: Based on gene therapy guidelines of the Ministry of Food and Drug Safety (MFDS) of Korea, the potential undesirable effects of PP-P8 had to be investigated in intact small rodent or marmoset models prior to first-in-human (FIH) administration. The estimated doses of PP-P8 for FIH are 1.0× 1010 - 1.0× 1011 CFU/person (60 kg). Therefore, to perform toxicological investigations in non-clinical animal models, we orally administered PP-P8 at doses of 3.375 × 1011, 6.75 × 1011, and 13.5× 1011 CFU/kg/day; thus the maximum dose was 800- 8000-fold higher than the estimated dose for FIH.Results: In our animal models, we observed no adverse effects of PP-P8 on clinicopathologic findings, relative organ weight, or tissue pathology. In addition, we observed no inflammation or ulceration during pathological necropsy.Conclusion: These non-clinical toxicology studies could be used to furnish valuable data for the safety certification of PP-P8.Keywords: biologics, therapeutic protein, probiotics derived anti-cancer protein P8, Pediococcus pentosaceus SL4, Lactobacillus rhamnosus, colorectal cancer, drug delivery system, protein secretion system, oral administration, non-clinical trial, toxicology finding